2019
DOI: 10.1093/jn/nxz155
|View full text |Cite
|
Sign up to set email alerts
|

l-Glutamine Represses the Unfolded Protein Response in the Small Intestine of Weanling Piglets

Abstract: Background Dysfunction of the endoplasmic reticulum (ER) results in apoptosis, inflammation, and enhanced proteolysis in the small intestine of humans and animals. l-Glutamine (Gln) is required for intestinal mucosal homeostasis in piglets. However, a functional role of the ER in the enterocytes of weanling piglets and its contribution to intestinal mucosal integrity remain largely unknown. Objective This study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This suggests that the differences in blood transcriptome that were observed in the quarantine nurserymay reflect responses to subclinical or minor infectious disease and/or to non-infectious stressors such as weaning, transportation, and mixing. For example, He et al [ 32 ] reported that the unfolded protein response pathway related to endoplasmic reticulum stress was activated in the small intestine of pigs due to weaning. As reviewed by Gimsa et al [ 33 ], the immune system and stress response are closely associated in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the differences in blood transcriptome that were observed in the quarantine nurserymay reflect responses to subclinical or minor infectious disease and/or to non-infectious stressors such as weaning, transportation, and mixing. For example, He et al [ 32 ] reported that the unfolded protein response pathway related to endoplasmic reticulum stress was activated in the small intestine of pigs due to weaning. As reviewed by Gimsa et al [ 33 ], the immune system and stress response are closely associated in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies Gln has been supplemented as single AA [ 34 36 ] or as dipeptide [ 29 , 33 ], with most of the control groups supplemented with isonitrogenous amounts of alanine (Ala). Studies supplementing Gln to piglets during the later suckling period, analyzing parameters after weaning, have been conducted as well [ 33 , 37 39 ]. Studies with lactating sows suggest that the Gln provided by milk might be limiting for protein synthesis of piglets [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The jejunum and liver were treated with RIPA lysis buffer to extract the total protein, and the concentrations were evaluated using a BCA assay. Then, protein abundances were measured as described previously . Briefly, proteins were separated by 10% SDS-PAGE following transfer to the PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Then, protein abundances were measured as described previously. 23 Briefly, proteins were separated by 10% SDS-PAGE following transfer to the PVDF membrane. After blocking with 3% BSA for 1 h, the bands were incubated with the primary antibody overnight at 4 °C and then were incubated with the secondary antibody for 1 h at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%